2012
DOI: 10.1021/es303570v
|View full text |Cite
|
Sign up to set email alerts
|

Organosulfates in Humic-like Substance Fraction Isolated from Aerosols at Seven Locations in East Asia: A Study by Ultra-High-Resolution Mass Spectrometry

Abstract: Humic-like substances (HULIS) in ambient aerosols collected at seven locations in East Asia were analyzed using electrospray ionization (ESI) coupled with an ultra-high-resolution mass spectrometer (UHRMS). Locations included a 3 km high mountaintop site in Taiwan, rural, suburban, and urban locations in the Pearl River Delta (PRD), South China, and in Taiwan. Organosulfates (OS) in the HULIS fraction were tentatively identified through accurate mass measurements and MS/MS spectra interpretation. In the two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
242
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(275 citation statements)
references
References 64 publications
26
242
5
1
Order By: Relevance
“…In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006). In this study, the required solid-phase extraction step precluded the detection of isoprene-derived organosulfates, which would have been removed prior to analysis.…”
Section: Biogenic Influencesupporting
confidence: 85%
“…In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006). In this study, the required solid-phase extraction step precluded the detection of isoprene-derived organosulfates, which would have been removed prior to analysis.…”
Section: Biogenic Influencesupporting
confidence: 85%
“…A solution of camphor sulfonic acid (Sigma-Aldrich, USA) was used to optimize ionization and fragmentation parameters to gain high intensity of [M−H] − , the resulting ionization voltage was 4 kV and the fragmentor was 120 V. 34 S-containing isotopic peaks coincident with the target ions provided an additional confirmation of 32 Scontaining formulas. 35 For pNOSs, additional MS/MS product ions with m/z 247 (loss of HNO 2 ) and m/z 231 (loss of HNO 3 ) were detected. 9 The structures of three pNOS isomers with MW 295 (pNOS a , pNOS b , pNOS c ) were identified by comparing the detected spectra (Figure S2c−e) with those provided by Surratt et al 9 The isomer pNOS a was identified by extremely low intensity of m/z 231 ions and high intensity of m/z 220 (loss of CO and NO 2 ) in MS2 spectra ( Figure S2c); while the isomer pNOS c was identified by significant intensity of m/z 142 ( − OSO 3 NO 2 ) ( Figure S2e).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…These species do not partition to dry particles (Kroll et al, 2005;Nguyen et al, 2014), so their condensed-phase products are called aqueous SOA (aqSOA; Ervens et al, 2011). IEPOX uptake also depends on the inorganic composition and acidity of the seed particles (Surratt et al, 2010;Gaston et al, 2014;Budisulistiorini et al, 2017;Lin et al, 2012;Riedel et al, 2015). A body of work indicates that the uptake of water-soluble organic gases into atmospheric waters (clouds, fogs, and aerosol water) is an important pathway for SOA formation (Ervens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%